Conhecimento, atitude e prática de presidiárias quanto ao uso do preservativo masculino e feminino - Nicolau, Ana Izabel Oliveira (2010)
Given the greater vulnerability to acquisition of Sexually Transmitted Diseases (STD)/HIV by women prisoners, decided to develop the study. It is an evaluative study of type Knowledge, Attitude and Practice (KAP) held in a female prison in the state of Ceará, with the following objectives: Assess the knowledge, attitude and practice regarding the use of prisoners male and female condoms as a measure prevention of STD/HIV; Verify the sociodemographic, sexual, reproductive and lifestyle habits of prisoners; Investigate vulnerability factors in prisoners; Associate predictor variables with the knowledge, attitude and practice of male and female condoms by prisoners; Compare the knowledge and attitude to the practice of male and female condoms by prisoners. Search with quantitative approach, involving a sample of 155 prisoners. Data collection was conducted from January to March 2010. The instrument included data on sociodemographics, sexual, reproductive and lifestyle habits. Then we applied the KAP survey about condoms, adapted from research Brenna et al. (2001). The data were compiled, stored and associated in the Statistical Package for Social Sciences (SPSS) version 17.0. The chi-square test was used as statistical tool. The sociodemographic profile pointed to a majority of young Brazilian, single, low education level and family income, trapped for drug trafficking. The history of sexual precocity revealed the occurrence of first sexual intercourse, stability and little variety of sexual partners. However, drug use, be male or female prisoner, and has tattoos/ piercings were the principal characteristics of the partnerships. The homo/ bisexuality and prostitution was attended by about 35%. STDs acquired before or after the arrest showed low percentages, 13.5% and 5.8% respectively. Only 15% were granted the right to conjugal visits. Smoking habits, alcoholism, and illicit drug use were presented in more than 60% of women. Knowledge about condoms proved to be superficial. Although they had heard of and/ or correctly knew the reasons for use, 120 (77.4%) couldn’t report three necessary cares for the proper use of male condoms and 143 (92.3%) females. Were diagnosed less favorable attitudes about the use of female and during oral sex. The practice proper condom had little representation, particularly females. Homosexuality, gender issues, lack of knowledge and access difficulties represented obstacles. The attitude was significantly associated with the variables age and age of first sexual intercourse. The proper use of condoms and the history of prostitution were statistically associated. The components of the KAP didn’t showed statistical associations between them. Therefore, knowledge and attitudes weren’ot adequate enough to ensure appropriate practices. Possible clarifications are in the context of difficulties in negotiating the use of the partners, restricting access and the "illegality" that occur in homosexual relations. Strengthening the autonomy of individuals, as the essence of the educational process, and consider the knowledge and opinions, should bring together the contexts of environmental vulnerability, social, cultural and emotional.